Correction: Aromatic sulfonate anion-induced pseudorotaxanes: environmentally benign synthesis, selectivity, and structural characterization. Issue 10 (15th December 2014) - Gong, Han-Yuan; Tang, Feng; Rambo, Brett M.; Cao, Rui; Xiang, Jun-Feng; Sessler, Jonathan L.
Abstract : Correction for 'Aromatic sulfonate anion-induced pseudorotaxanes: environmentally benign synthesis, selectivity, and structural characterization' by Han-Yuan Gong et al., Chem. Commun., 2015, DOI: ; Web:10.1039/c4cc08284b .